The Potential Applications of Hyaluronic Acid Hydrogels in Biomedicine - Ahmadian, Elham; Dizaj, Solmaz Maleki; Eftekhari, Aziz; Dalir, Elaheh; Vahedi, Parviz; Hasanzadeh, Amir; Samiei, Mohammad (Drug Research, 2020)
Hyaluronic acid (HA) is widely used in the biomedicine due to its biocompatibility, biodegradability, and nontoxic properties. It is crucial for cell signaling role during morphogenesis, inflammation, and wound repair. After hydrogel formation, HA easily is converted to elastic sheets in order to use in preclinical and clinical applications. In addition, HA-derived hydrogels are easily used as vectors for cell and medication in tissue repairing and regenerative medicine. Moreover, in comparison with other polymers, HA -based hydrogels play a key role in in cellular behavior, including stem cell differentiation. The current paper reviews both basic concepts and recent advances in the development of HA-based hydrogels for biomedical applications.
Keywords: regenerative medicine; drug delivery; biopharmaceuticals